2021
DOI: 10.1002/ijc.33756
|View full text |Cite
|
Sign up to set email alerts
|

Definitive evidence for Club cells as progenitors for mutant Kras/Trp53‐deficient lung cancer

Abstract: Accumulating evidence suggests that both the nature of oncogenic lesions and the cell‐of‐origin can strongly influence cancer histopathology, tumor aggressiveness and response to therapy. Although oncogenic Kras expression and loss of Trp53 tumor suppressor gene function have been demonstrated to initiate murine lung adenocarcinomas (LUADs) in alveolar type II (AT2) cells, clear evidence that Club cells, representing the second major subset of lung epithelial cells, can also act as cells‐of‐origin for LUAD is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…This is consistent with the hypothesis that NSCLC cells origin from AT2 cells or secreting (e.g. club) cells ( 45–47 ).…”
Section: Resultssupporting
confidence: 92%
“…This is consistent with the hypothesis that NSCLC cells origin from AT2 cells or secreting (e.g. club) cells ( 45–47 ).…”
Section: Resultssupporting
confidence: 92%
“…Remarkably, regardless of the originating cell type, all Eml4-Alk tumours were positive for the AT2 cell marker, SPC. In line with this observation, Rosigkeit et al 28 have recently shown that Club-originated tumours become AT2-like by expressing SPC. DNA methylation was shown to act as cellular memory, storing information on previous differentiation states 37 .…”
Section: Discussionmentioning
confidence: 56%
“…At the early stages of tumorigenesis, Eml4-Alk induced early hyperplasia in the bronchi that partially lost the Club cell marker CCSP, and acquired alveolar markers such as SPC, similar to Kras mutant LUAD, described by the authors in ref. 28 (Fig. 1b, c ).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations